Effect of Ultrasound Time on Structural and Gelling Properties of Pea, Lupin, and Rice Proteins - Arancibia-Aguilar, C; Riquelme-Hinojosa, N (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Plant proteins are garnering interest due to the growing demand for plant-based products, but their functionality in gel-based foods remains limited. Ultrasound (US) technology may improve the technological properties of proteins. Thus, the effect of US treatment time (0–15 min) on the structure and gelling properties of pea, lupin, and rice proteins was evaluated. The results showed that the whiteness (~60%) of all freeze-dried proteins remained unchanged (p > 0.05), regardless of the US time. However, FT-IR analysis revealed progressive reductions in α-helix and β-sheet for pea and lupin proteins (~50%) with US time, indicating partial unfolding. In addition, microstructure analysis showed an ~80% reduction in aggregate size for these proteins, while rice protein exhibited minimal changes. Conversely, weak gels were formed with pea and lupin proteins treated after 5 and 10 min of US, respectively, whereas rice protein did not form gels. Furthermore, US treatment time significantly increased (p < 0.05) the mechanical moduli, resulting in more structured gels after longer treatment times (tan δ ~0.3 at 15 min of US). These findings suggest that US treatment enhances the gelling properties of pea and lupin proteins, making them more suitable for plant-based food applications such as yogurt or desserts. © 2025 by the authors.